Cannabichromene: integrative modulation of apoptosis, ferroptosis, and endocannabinoid signaling in pancreatic cancer therapy - Yu-Na Hwang; Ju-Hee Park; Han-Heom Na; Tae-Hyung Kwon; Jin-Sung Park; Sehyun Chae; Young Taek Oh; Keun-Cheol Kim (Cell Death Discovery)
Abstract Cannabichromene (CBC: C21H3O2, M.W.: 314.46 g) is a non-psychotropic phytocannabinoid derived from Cannabis sativa (hemp), and its potential therapeutic properties have attracted increasing attention. Specifically, it has demonstrated strong anti-inflammatory effects in animal models of edema through non-CB receptor mechanisms; however, further pharmacological studies based on cancer models are required. In this study, we investigated the molecular mechanisms underlying the anti-cancer activity of CBC in human pancreatic cancer cells. Through mRNA-seq analysis, the expression levels of many genes involved in cell death pathways were upregulated or downregulated after CBC treatment, and these included ferroptosis-related genes, such as HMOX1. We further confirmed the functional validity of apoptosis and ferroptosis induction after CBC treatment using various molecular assays. In addition, CBC preferentially increased the expression of TRPV1 and CB2. Accordingly, the effects on cell death were reversed after treatment with TRPV1 and CB2 inhibitors, suggesting that receptor expression is necessary for the induction of apoptotic cell death. Finally, we confirmed the consistent regulation of apoptosis, ferroptosis, and endocannabinoid receptors during tumor growth inhibition after CBC treatment using in vivo xenograft models. Therefore, we propose that CBC exhibits pharmacological activity via the integrative modulation of multiple cell death pathways, which can be exploited for pancreatic cancer therapy.